Electronic Recording Culture among Maternal and Child Health Workers: A Case Study of E-RM Implementation at Adina Wonosobo Maternity Hospital - Hidayati Gusri, Suci; Mugihartadi (INDOGENIUS, 2025)
Background & Objective: Digitalization in healthcare systems has driven the implementation of electronic medical records (EMR) as the primary means of improving the efficiency and quality of medical documentation. However, the successful implementation of EMR in specialized hospitals such as RSIA is greatly influenced by the work culture and recording practices of healthcare workers. This study aims to explore the electronic documentation culture among maternal and child healthcare workers at RSIA Adina Wonosobo, focusing on user perceptions, socio-cultural barriers, and adaptation strategies toward the EMR system. Method: This study employs a qualitative approach with an intrinsic case study design. Data were collected through semi-structured in-depth interviews, non-participatory observation, and document review. Analysis was conducted using a thematic approach through inductive coding stages. Result: The study findings indicate that healthcare workers' perceptions of EMR are ambivalent; the system is seen as facilitating data access but also increasing administrative burdens. Cultural barriers such as the dominance of manual record-keeping, resistance to change, and low participation in system design pose significant challenges. However, adaptive strategies were identified among younger healthcare workers, including peer training, utilization of underutilized system features, and hybrid record-keeping practices. Conclusion: The implementation of EMR in RSIA requires a socio-technical approach that is responsive to the values, perceptions, and work practices of healthcare workers. This study emphasizes the importance of user involvement in the digital transformation process and offers policy recommendations to strengthen a sustainable electronic recording culture in maternal and child health facilities.